Diab Res Open Access 2020
DOI: 10.36502/2020/droa.6167
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hba1c, decreased HDL and Abdominal Obesity in Prediabetics of Karnataka State, South India

Abstract: This study aims to explore the possibility of the existence of dyslipidemia among prediabetics in India and to find the correlation if any, present between their glycated hemoglobin (HbA1c) levels and their lipid profile, and to identify the risk factor(s) if any, for the onset of diabetes. A cross-sectional study involving 212 individuals in Bangalore of Karnataka State, India from the period of August 2017 to February 2019 was considered for the study. Within the lipid profile, High-Density Lipoprotein (HDL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…BMI did not show any significant association with prediabetes. [9] Similarly, in a study of myocardial performance index in prediabetes and its correlation with other cardiovascular risk factors, assessment of lipid profile, BMI, Waist Hip Ratio (WHR), it was noted that BMI, WHR, TC, TG, LDL, VLDL were all significantly higher and HDL was significantly lower in prediabetes subjects [12] The current study also showed similar results with levels of LDL, triglycerides and total cholesterol increasing as the HbA1c levels increase and the HDL levels reducing inversely with respect to HbA1c. Analysis of the data obtained by Korea National Health and Nutrition examination survey from the study of their prediabetics had shown significantly higher levels of Total TC, TG, LDL, TC to HDL-C ratio, TG to HDL-C ratio, LDL-C to HDL-C ratio, and significantly increased urinary albumin excretion in prediabetic women [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI did not show any significant association with prediabetes. [9] Similarly, in a study of myocardial performance index in prediabetes and its correlation with other cardiovascular risk factors, assessment of lipid profile, BMI, Waist Hip Ratio (WHR), it was noted that BMI, WHR, TC, TG, LDL, VLDL were all significantly higher and HDL was significantly lower in prediabetes subjects [12] The current study also showed similar results with levels of LDL, triglycerides and total cholesterol increasing as the HbA1c levels increase and the HDL levels reducing inversely with respect to HbA1c. Analysis of the data obtained by Korea National Health and Nutrition examination survey from the study of their prediabetics had shown significantly higher levels of Total TC, TG, LDL, TC to HDL-C ratio, TG to HDL-C ratio, LDL-C to HDL-C ratio, and significantly increased urinary albumin excretion in prediabetic women [13].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia or abnormal lipid profile levels plays a crucial role in atherogenesis, in both prediabetes and diabetes, characterized by elevated triacylglycerol (TG), reduced high-density lipoprotein (HDL), and predominant small density-low density lipoprotein (LDL). Dyslipidemia and its correlation with HbA1c and fasting blood glucose (FBG) has been studied extensively in diabetic patients, but very few studies have been done so far among prediabetes individuals on their lipid profile pattern and its possible correlation with FBG or HbA1c (9).…”
Section: Introductionmentioning
confidence: 99%